Assessing and understanding food safety risk practices in Nairobi pork food system: A value chain approach - Murungi, M.K.; Muinde, P.; Akoko, James M.; Rushton, Jonathan; Fèvre, Eric M.; Domínguez Salas, Paula; Muloi, Dishon M.; Häsler, Barbara; Alarcón, Pablo (Iowa State University, 2015)
In Nairobi the pork food system may represent a major source of zoonotic pathogens. Yet, the system and its public health risks have not been described. The study address this gap by identifying and understanding food safety risks practices in the Nairobi pork food system using a value chain approach.